Employee Error: The Development, Validation, and Use of a Perceived Error Measure for Predicting Rumination, Burnout, and Counterproductive Work Behaviors - Carroll, Anne C (East Carolina University, 2023)
Errors are ubiquitous in organizations. Nonetheless, scholarly literature regarding workplace error has largely focused on low-rate catastrophic failures such as the Challenger, Columbia, and Chernobyl accidents. However, errors are not always large in scale nor rare. A general measure of perceived error will be useful for industries that want to understand the relationship between employee error and important job-related outcomes such as rumination, burnout, and counterproductive work behaviors (CWBs). In order to better understand this area, we created and validated a perceived error scale (PES) on a general population of full-time workers. Study one consisted of 440 observations collected via MTurk. An exploratory factor analysis was conducted on 60 percent of the data, and a confirmatory factor analysis was conducted on the remaining sample. Based on psychometric analysis, we determined that perceptions of error were consistent with three established categories of error: individual, latent, and planning errors. Study two utilized a cross-sectional design consisting of 314 observations. SEM was used in this study to test a sequential mediation model. The results suggested that how an individual perceives error may impact rumination, burnout, and CWBs. Both the relationship between latent errors and CWBs were mediated by rumination and burnout. Similarly, the relationship between individual errors and CWB was mediated by rumination and burnout. Planning errors were not related to any of the downstream variables in the model. This is consistent with goal progress theory and the stressor-emotion model of CWB. Notably, the PES factor structure was replicated in the second study adding to its reliability evidence. Future research may consider taking a more longitudinal approach to measuring perceptions of error, burnout, rumination, and CWBs.
Keywords: CWB; Counterproductive work behaviors; stressor-emotion model of CWB; rumination; medical errors; errors; perception of error; perceived error scale; error management; aggression; Industrial hygiene; Burn out (Psychology)--Prevention; Organizational behavior